Epidemiology of Hepatitis A virus in Africa among Persons Aged 1–10 years: a systematic review protocol - Kanyenda, Tiwonge J.; Abdullahi, Leila H.; Hussey, Gregory D.; Kagina, Benjamin M. (Systematic Reviews, 2015)
Africa is considered an area of high endemicity for hepatitis A virus infection. However, in the past two decades, tremendous progress has been made in improving water sources and sanitation which are risk factors for hepatitis A virus infection. Recent studies suggest that several African countries could be in epidemiological transitions due to the evident socio-economic development. As a result, there may be a decrease in the exposure to and infection with hepatitis A virus at an early age. Understanding and mapping the shifting epidemiology is vital in developing control measures against the disease. We are conducting a comprehensive systematic review study to document the current burden of hepatitis A virus infection in Africa.
Keywords: Epidemiology; hepatitis A virus